The impact of formal transformations in the structure of architectural identity Duhok city case study - Sideeq, Siber Jameel; Fathy, Ihsan Abdulwahab; Ali, Alan Faraydoon (Sulaimani Journal for Engineering Sciences, 2019)
The architectural identity has witnessed a problem and transformation in its form and context as a result of community contact with other civilizations. Therefore, in order to realize these formal transformations and architectural identity problem, this research focused on diagnosing the relationship and the impact of formal transformations with its types and different levels on the formative structure of architectural identity. So the research problem is emerged and represented by the “lack of knowledge clarity related to the nature of formal transformations impact and their different levels on the formative structure of architectural identity in Duhok city. And the objective of the research is to "determine the level of influence of these formal transformations in the structure of the architectural identity products in Duhok city." The research was carried out within the theoretical framework (structural approach) in uncovering the variables associated with the transformative structure within the architectural identity, and then applied this framework to selected architectural models from Dohuk city, to analyze the results and determine the conclusions.
Keywords: Formal transformations; Architectural Identity; Duhok City